Comparative analysis of hemostatic efficacy and safety: absorbable gelatin sponge with hemostatic fluid gelatin vs. tranexamic acid in posterior cervical expansive open-door laminoplasty - Yang, Yu; Cao, Donghui; Li, Xusheng; Zhang, Xiao; Tian, Yanrong; Mao, Pengcheng; Yuan, Haifeng (Frontiers in Surgery, 2025)
BackgroundPosterior cervical expansive open-door laminoplasty carries significant intraoperative bleeding risks from Batson's plexus. While hemostatic agents such as absorbable gelatin sponge (GS), hemostatic fluid gelatin (HFG), and tranexamic acid (TXA) are widely used in spinal surgery, the efficacy and safety of combined strategies remain underexplored. This study aims to compare the hemostatic efficacy and safety of GS combined with HFG vs. GS combined with intravenous TXA in posterior cervical expansive open-door laminoplasty.MethodsA retrospective analysis was conducted on 75 patients undergoing posterior cervical expansive open-door laminoplasty at Ningxia Medical University General Hospital from January 2022 to January 2024, with stratification into two groups based on intraoperative hemostatic materials: the GS-HFG group (absorbable gelatin sponge combined with hemostatic fluid gelatin, n = 30) and the GS-TXA group (absorbable gelatin sponge combined with intravenous tranexamic acid, n = 45), with subsequent comparison of baseline demographics, operative duration, intraoperative blood loss, total postoperative drainage volume, Visual Analog Scale (VAS) pain scores, Japanese Orthopaedic Association (JOA) functional assessments, postoperative adverse events, and complications.ResultsOperative duration demonstrated no statistically significant difference between the GS-HFG and GS-TXA groups (139.9 ± 21.7 min vs. 144.4 ± 30.7 min; p > 0.05), with intraoperative blood loss measuring 135 ± 29.1 ml vs. 145 ± 29.4 ml (mean difference: −10 ml; 95% CI: 134.9–144.7 ml; p > 0.05), and postoperative drainage volumes recorded at 200.65 ± 48.92 ml vs. 186.24 ± 52.18 ml (p > 0.05). No significant differences were observed in preoperative/postoperative biochemical markers. Complications included axial symptoms (1 case in GS-HFG, 3 in GS-TXA) and C5 nerve root palsy (1 case in each group). No thromboembolic events or other adverse reactions occurred.ConclusionBoth the GS-HFG and GS-TXA protocols effectively reduce perioperative bleeding without increasing the risk of complications in posterior cervical expansive open-door laminoplasty.